Interpretation of the mass possession in Morzine by contemporary Austrian press - Peter Ondreička (Theatrum Historiae)
This paper describes the mass possession in Morzine in the mid-nineteenth century. The main aim is to analyse how the contemporary media reflected such a case of possession. Contemporary articles presented six discourses. In the first discourse, we can find descriptions of Morzine as a remote area where superstitions still survived. The second discourse is a reflection of Morzine as a wonder or sensation. The next discourse focuses on the description of the condemnation of Morzine as a case of superstitions belonging to the past. The case of Morzine as a disease of women is presented in the fourth part of the study. The last two discourses focus on the medical context of the case and the connection of the symptoms to Christianity.